An Empirical Study: Understanding The Influence of Responsiveness, Reliability, And Assurance On Customer Satisfaction In Online Banking Services (People's Journal of Management, 2024)
This article investigates the influence of responsiveness, reliability, and assurance on customer satisfaction in online banking, utilizing a sample size of 137 participants. The findings, which were obtained through thorough statistical research, show that, in the context of online banking, there is a positive and substantial association between these important parameters and customer satisfaction. According to the research, customer satisfaction is positively impacted by responsiveness, which is defined as the timely and efficient response of customer questions and issues, significantly influenced by reliability, which is a measure of the consistency and dependability of online banking services. Additionally, our study emphasizes how important assurance is in determining how satisfied customers are with online banking services. Establishing trust and confidence among online banking customers is crucial, as seen by the positive correlation between assurance and customer satisfaction.